Adding tests to risk based guidelines: evaluating improvements in prediction for an intermediate risk group. (7th September 2016) - Paynter, Nina P; Cook, Nancy R
Abstract : Using an additional test in patients who are not at high enough risk of developing disease to confidently treat, or low enough risk to confidently not treat would seem to be a straightforward way to resolve the clinical equipoise and is recommended by many guidelines. However, clear methods for evaluating the population utility of additional tests in this group have not been established. This paper includes worked examples and simulation data to show that focus on the intermediate risk group alone can be misleading and that population utility is best evaluated across the full range of risk.